Holistic scientific approach to address wall damage and berm loss from blasting in large open cut metal mines - Tapan Goswami; Stephen Jeric; Geoff Brent (International Society of Explosives Engineers, 2011)
Highwall failures in large deep open cut mines have very significant safety and commercial implications. There are many factors influencing the stability of highwalls. The major influence is the interaction of the local geology with the shape of the pit wall. This factor is in the realm of the geotechnical engineer and is beyond the control of the blasting engineer. However, a secondary influence is the blastinduced damage to the wall. In most open cut metal mines the blasting strategy to control this damage involves the use of separate production and trim blasts bounded by presplits at the final wall.